PERAN MEDIASI MOTIVASI INTRINSIK PADA PENGARUH DUKUNGAN LINGKUNGAN KERJA DAN DUKUNGAN LINGKUNGAN NON KERJA TERHADAP KREATIVITAS KARYAWAN - Anggia Paramitha (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2017)
Nowadays, no business organization can escape from a stiffer competition. Thissituation demands for never ending innovation to survive and grow. Arguably, an innovative organization cannot be achieved without creative employees and supporting working environment. This study aims at investigating the relationship of the environment support on the employees' creativity. The environment support, in this study, includes work and non-work environment support, such as the support from supervisor and family. Special attention is paid to assess the mediating role of intrinsic motivation in the relationship. In doing so, a survey is administered to 132 employees (editorial staffs) working in mass media industry in the Indonesian context.The findings show that the support from co-workers is influential to promote the creativity of the employees. Surprisingly, the supports from supervisor and family provide no significant impact on the creativity. The study also reveals that intrinsic motivation partially influences the relationship between the support from co-workers and the creativity. It unearths that intrinsic motivation the employees have may signify the impact of the support from co-workers on their creativity. But this is not the case for the supports from supervisor and family.